¿ES LA RESPONSABILIDAD SOCIAL UNIVERSITARIA VERDADERA RESPONSABILIDAD SOCIAL UNIVERSITARIA?: UN ANÁLISIS JURÍDICO - Chang Chuyes, Guillermo (Revista de Derecho, 2022)
This article analyzes the law about university social responsibility in Peru. First, it has detailed how social responsibility has become a goal to the universities and why it has been studied by the business literature. Then, in the case of law, university social responsibility corresponds to the principle of solidarity. Finally, Peruvians laws about this issue has been analyzed.